Effects of biosolids application on pasture and grape vines in south-eastern Australia - Nash, D.; Butler, C.; Cody, J.; Warne, M.; McLaughlin, M.; Heemsbergen, D.; Broos, K.; Bell, M.; Barry, G.; Pritchard, Deborah; Penney, N. (Hindawi Publishing Corporation, 2011)
Biosolids were applied to a pasture and a vineyard in south-eastern Australia. At both sites, soil Cd, Cu, and Zn concentrations linearly increased with biosolids application rates although not to the extent of exceeding soil quality guidelines. Biosolids marginally increased soil C and N concentrations at the pasture site but significantly increased P concentrations. With lower overall soil fertility at the vineyard, biosolids increased C, N, and P concentrations. At neither site did biosolids application affect soil microbial endpoints. Biosolids increased pasture production compared to the unfertilised control but had little effect on grape production or quality. Interestingly, over the 3-year trial, there was no difference in pasture production between the biosolids treated plots and plots receiving inorganic fertiliser. These results suggest that biosolids could be used as a fertiliser to stimulate pasture production and as a soil conditioner to improve vineyard soils in this region